Five Steps to Seasonal Savings - Ricki McWilliams; Julie Pigott-Dillard; Michael Gutter (EDIS)
When the holiday season is over you may find yourself saying: “Why did I spend all of that money? Why did I wait until the last minute to shop? I don’t even want to think about how long it will take to pay off the credit cards. I hope I didn’t take too much money out of the ATM. Did I buy my mom the same gift twice? I should have had a plan.” By following a few simple steps, you can end this post-holiday hangover. This 5-page fact sheet was written by Ricki McWilliams, Julie Pigott-Dillard, and Michael Gutter, and published by the UF Department of Family, Youth and Community Sciences, January 2014.